Programming in Visual Basic 2008 - Bradley, Julia Case (McGraw-Hill, 2009)
The author team of Bradley and Millspaugh remain the guiding light in Programming with Visual Basic 2008 for countless students around the world. This updated edition of their bestseller contains examples, feedback questions, screen captures, step-by-step exercises, and thorough appendices.